2022
DOI: 10.1186/s12886-022-02620-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different correction formulas and measurement methods for the accurate determination of intraocular pressure after SMILE and FS-LASIK surgery

Abstract: Background To compare the accuracy of non-contact tonometry, Pentacam, and corneal visualization Scheimpflug technology (Corvis ST) for the measurement of intraocular pressure (IOP) after small incision lenticule extraction (SMILE) or femtosecond laser-assisted in situ keratomileusis (FS-LASIK) surgery. Methods A total of 49 patients (98 eyes) undergoing FS-LASIK or SMILE surgery at West China Hospital, Sichuan University from January to March 2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Some studies have reported that IOP after LASIK is underestimated 6,10 . IOP reduction after this procedure has been attributed to a reduction in CCT 6,11,10 . However, changes in corneal stiffness after a surgical procedure such as LASIK can be an equally important reason 10 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies have reported that IOP after LASIK is underestimated 6,10 . IOP reduction after this procedure has been attributed to a reduction in CCT 6,11,10 . However, changes in corneal stiffness after a surgical procedure such as LASIK can be an equally important reason 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies and experiments in animal models have shown that keratorefractive surgery does not induce a decrease in IOP, suggesting that the reduced IOP measurements recorded after surgery need to be corrected 11,15 . To minimize GAT biases in post LASIK patients, some authors have postulated that non-contact tonometer is more accurate than the GAT 4,16 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations